HISTORY OF THE DEVELOPMENT OF ANCIENT EASTERN PHILOSOPHY - Timur Abduvalievich Madalimov (Western European Studies, 2024)
This article analyzes the emergence of philosophical ideas that arose in the ancient East, especially in Babylon, Mesopotamia, India and China.
Keywords: svilization; dao; yin-yan